2014
DOI: 10.1007/978-3-319-10428-7_43
|View full text |Cite
|
Sign up to set email alerts
|

Automatically Improving Constraint Models in Savile Row through Associative-Commutative Common Subexpression Elimination

Abstract: When solving a problem using constraint programming, constraint modelling is widely acknowledged as an important and difficult task. Even a constraint modelling expert may explore many models and spend considerable time modelling a single problem. Therefore any automated assistance in the area of constraint modelling is valuable. Common sub-expression elimination (CSE) is a type of constraint reformulation that has proved to be useful on a range of problems. In this paper we demonstrate the value of an extensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 12 publications
0
30
0
Order By: Relevance
“…We focus herein on reformulation of the constraint modelling language Essence Prime [49], using the constraint modelling assistant Savile Row [47,50]. Essence Prime is similar to other constraint modelling languages such as OPL and MiniZinc.…”
Section: Constraint Programming Propositional Satisfiability and Tamentioning
confidence: 99%
“…We focus herein on reformulation of the constraint modelling language Essence Prime [49], using the constraint modelling assistant Savile Row [47,50]. Essence Prime is similar to other constraint modelling languages such as OPL and MiniZinc.…”
Section: Constraint Programming Propositional Satisfiability and Tamentioning
confidence: 99%
“…Using Conjure to refine the streamlined specifications into constraint models, solved with Savile Row 1 [19] and Minion 2 [10], candidates are evaluated against instances of the specified class. Effective streamliners are combined to produce more powerful candidates.…”
Section: Figmentioning
confidence: 99%
“…This is an important step because it allows us to leverage the rich modelling languages available in constraints such as MiniZinc [26] and Essence Prime [20]. We have previously shown that the constraint modelling tool SAVILE ROW [17] can be used to translate constraint problems directly to SAT, exploiting automated modelling techniques such as common subexpression elimination [21]. We add to the important and growing literature on modelling of constraints in SAT [6].…”
Section: Introductionmentioning
confidence: 99%